Investigation of antimicrobial activity and chemical constituents of Momordica charantia L. var. abbreviata Ser - Dam, Nguyen Phuc; Dien, Vo Minh; Thanh, Luong Huynh Vu; Hien, Phan Thi Thanh; Tram, Nguyen Thi Thu (Vietnam Journal of Science and Technology, 2019)
The antimicrobial potential of the four extracts of Momordica charantia L. var. abbreviata Ser was screened against four bacterial and four fungal strains, using microbroth dilution assay. The chloroform extract showed the highest growth inhibitory activity. Phytochemical study on the bioactive chloroform extract led to the isolation of four known compounds as octadecan-1-ol (1), (23E)-5β,19-epoxycucurbita-6,23,25-trien-3β-ol (2), 5α-poriferasta-7,25-dien-3β-ol (3) and 3-O-(6′-O-palmitoyl-β-D-glucopyranosyl)-clerosterol (4). Their structures were elucidated by spectroscopic methods including 1D and 2D-NMR, MS and in comparison with literature data. Here, such metabolites were reported for the first time in M. charantia L. var. abbreviata Ser.